Parenting Education and Support for Parents - Pranata, Lilik; Daeli, Novita Elisabeth; Fruitasari, MK. Fitriani; Frisca, Sanny; Anggraini , Novita; Sri Sumiyati, Teresia (Jurnal Ragam Pengabdian, 2026)
Parenting plays an important role in supporting children’s growth and development; however, many parents still have limited knowledge regarding appropriate parenting practices and effective family communication. This community service program aimed to improve participants’ knowledge about family parenting through health education. The program used an educational intervention method consisting of lectures, discussions, and interactive question-and-answer sessions. Evaluation was conducted using a pretest-posttest design involving 27 participants to assess knowledge changes before and after the intervention. The pretest results showed that participants’ knowledge scores ranged from 25 to 70, indicating low to moderate baseline understanding. After the educational intervention, posttest scores increased significantly, ranging from 75 to 100, with most participants scoring above 85. All participants showed improved scores, demonstrating the effectiveness of the educational program in increasing knowledge. Participant satisfaction evaluation also revealed positive responses, with most participants agreeing or strongly agreeing that the topic was interesting, the materials were clearly delivered, and the activity was beneficial. Furthermore, participants expressed interest in attending future programs with different topics. These findings suggest that family parenting education is an effective strategy to improve parental knowledge and can be implemented as a promotive and preventive effort to support healthier family environments and better child development outcomes.